Social defeat-induced anhedonia: effects on operant sucrose-seeking behavior - Riga, Danai; Theijs, J. T.; De Vries, Taco J.; Smit, August B.; Spijker, Sabine (Frontiers in Behavioral Neuroscience, 2015)
Reduced capacity to experience pleasure, also known as anhedonia, is a key feature of the depressive state and is associated with poor disease prognosis and treatment outcome. Various behavioral readouts (e.g. reduced sucrose intake) have been employed in animal models of depression as a measure of anhedonia. However, several aspects of anhedonia are poorly represented within the repertoire of current preclinical assessments. We recently adopted the social defeat-induced persistent stress (SDPS) paradigm that models a maintained depressive-like state in the rat, including social withdrawal and deficits in short-term spatial memory. Here we investigated whether SDPS elicited persistent deficits in natural reward evaluation, as part of anhedonia. We examined cue-paired operant sucrose self-administration, enabling us to study acquisition, motivation, extinction and relapse to sucrose seeking following SDPS. Furthermore, we addressed whether guanfacine, an α2-adrenergic agonist that reduces stress-triggered maladaptive behavioral responses to drugs of abuse, could relief from SDPS-induced anhedonia. SDPS, consisting of 5 social defeat episodes followed by prolonged (≥8 weeks) social isolation, did not affect sucrose consumption during acquisition of self-administration. However, it strongly enhanced the motivational drive to acquire a sucrose reward in progressive ratio training. Moreover, SDPS induced initial resilience to extinction and rendered animals more sensitive to cue-induced reinstatement of sucrose-seeking. Guanfacine treatment attenuated SDPS-induced motivational overdrive and limited reinstatement of sucrose seeking, normalizing behavior to control levels. Together, our data indicate that long after the termination of stress exposure, SDPS induces guanfacine-reversible deficits in evaluation of a natural reward. Importantly, the SDPS-triggered anhedonia reflects many aspects of the human phenotype, including impaired motivation and goal-directed conduct.